PENGARUH PERAN KEPALA SEKOLAH DAN BUDAYA KERJA TERHADAP MOTIVASI BERPRESTASI GURU SEKOLAH DASAR DI KABUPATEN SEMARANG - Noor Miyono; Erny Dewi Astuti (JURNAL MANAJEMEN PENDIDIKAN, 2020)
THE EFFECT OF THE ROLE OF THE SCHOOL HEAD AND WORK CULTURE ON THE ACHIEVEMENT OF BASIC SCHOOL TEACHERS MOTIVATION IN SEMARANG DISTRICTThis study to determine (1) the effect of the principal's role on teacher achievement motivation. (2) the influence of work culture on teacher achievement motivation (3) the effect of the principal's role and work culture together on teacher achievement motivation. The population in this study was 269 elementary school teachers in Susukan subdistrict, Semarang regency, a sample of 161 teachers using proportional sampling sampling. The collection method uses a questionnaire. Data analysis using descriptive analysis, hypothesis testing consisting of simple and multiple regression using the SPSS for Window Release 21 program The research findings show that the role of the principal has a significant effect on teacher achievement motivation by 34.8%. Work culture has a significant effect on teacher achievement motivation by 34.1%, the role of school principals and work culture has a significant effect on teacher achievement motivation in SDN Susukan Semarang regency by 44.8%, with a regression equation Ŷ = 12.075 + 0.399X1 + 0.484X2. so the better the role of the principal and work culture, the teacher achievement motivation will also increase